CAVE-2 (Cetuximab-AVElumab) mCRC: A Phase II Randomized Clinical Study of the Combination of Avelumab Plus Cetuximab as a Rechallenge Strategy in Pre-Treated RAS/BRAF Wild-Type mCRC Patients - Napolitano, Stefania; Martini, Giulia; Ciardiello, Davide; Di Maio, Massimo; Normanno, Nicola; Avallone, Antonio; Martinelli, Erika; Maiello, Evaristo; Troiani, Teresa; Ciardiello, Fortunato (Frontiers in Oncology, 2022)
Introduction: Immunotherapy has limited efficacy in metastatic colorectal cancer (mCRC). Understanding mechanisms mediating immune resistance in microsatellite stable (MSS) colorectal tumors remains an ongoing challenge. Novel combination immunotherapy-based approaches have been developed under the rationale of overcoming immune resistance and developing effective immune response against colorectal tumor cells. Preclinical studies have demonstrated that cetuximab may modulate immune response to cancer cells. In this scenario, the inhibition of PD-L1 with IgG1 MAb avelumab in combination with anti-EGFR IgG1 monoclonal antibody cetuximab could be a strategy for potentiating antitumor activity. CAVE phase 2 single arm clinical trial provided the first evidence of clinical activity of combining cetuximab plus avelumab in 77 patients with RAS Wild-Type (WT) mCRC. This combination had a good toxicity profile, with a low rate of common grade 3 adverse events. Patients and Methods: Based on results obtained with CAVE clinical trial, here we describe the design and rationale for the Phase II, randomized CAVE 2 clinical study of the combination of avelumab plus cetuximab as rechallenge strategy in pre-treated RAS, BRAF WT mCRC patients treated in first line with chemotherapy in combination with cetuximab and have had a clinical benefit (complete or partial response) from treatment. 173 patients will be randomized (2:1) to cetuximab + avelumab (115) or cetuximab as single agent (58). Primary end point is Overall Survival. Key secondary end points include Overall Response Rate, Progression Free Survival and safety. For each patient, before treatment, a blood sample will be obtained and analyzed for circulating free tumor DNA according to NGS (Foundation/Roche), to identify RAS/BRAF WT patient to be enrolled. The same procedure will be performed at progression of the disease. Additional blood/plasma, tumor and fecal samples will be collected and centrally stored for additional translational studies. Discussion: This study will provide the rationale to test immunotherapy-based combinations in the clinical setting, offering new opportunities for RAS WT mCRC patients. Trial Registration: ClinicalTrials.gov Identifier: NCT05291156. Registered on March 22 2022.